2020
DOI: 10.1101/2020.03.19.999508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fidgetin-like 2 is a novel negative regulator of axonal growth and can be targeted to promote functional nerve regeneration after injury

Abstract: The microtubule (MT) cytoskeleton plays a critical role in axon growth and guidance. Here, we identify the MT severing enzyme fidgetin-like 2 (FL2) as a negative regulator of axonal regeneration and a potential therapeutic target for promoting neural regeneration after injury.Genetic knockout of FL2 in cultured adult dorsal root ganglion (DRG) neurons resulted in longer axons and attenuated growth cone retraction in response to inhibitory molecules. Given the axonal growth-promoting effects of FL2 depletion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In fact, a recent study by Baker et al, found that FL2 knockdown had a neuro-restorative effect on injured cavernous nerves in a rodent model. 43 The increase in the number of nerve clusters observed in the 10 µM and 20 µM of FL2-NPsi groups warrants further studies to assess for the possible neuro-restorative potential of this treatment (see Fig. 4 , see Supplement Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, a recent study by Baker et al, found that FL2 knockdown had a neuro-restorative effect on injured cavernous nerves in a rodent model. 43 The increase in the number of nerve clusters observed in the 10 µM and 20 µM of FL2-NPsi groups warrants further studies to assess for the possible neuro-restorative potential of this treatment (see Fig. 4 , see Supplement Fig.…”
Section: Discussionmentioning
confidence: 97%